Answer:
<h2>12 </h2>
Step-by-step explanation:
<h2>2.5x = 30</h2><h2>x = 30 / 2.5</h2><h2>x = 12</h2>
![\huge \pink{solution}](https://tex.z-dn.net/?f=%20%5Chuge%20%5Cpink%7Bsolution%7D)
Given :7x+6=5(x+2)
Now We will use the distributive property to multiply 5 by x+2.
→7x+6=5x+10
We will Subtract 5x from both sides.
→7x+6−5x=10
We will Combine 7x and −5x to get 2x.
→2x+6=10
We will Subtract 6 from both sides.
2x=10−6
We will Subtract 6 from 10 to get 4.
2x=4
We will Divide both sides by 2.
x= 4/2
At last,We Divide 4 by 2 to get 2.
x=2
Answer: 8.125 inches
Step-by-step explanation: Ok so if the plant grew 3.25 inches every month, and there were 2.5 months, you need to multiply 3.25 by 2.5 to get the total amount of growth. So that would be 8.125
Answer:
The actual distance between the cities is 211.67 cm.
Step-by-step explanation:
Given:
The map key indicates that 4.5 cm is equivalent to 75 cm.
Now, to find the actual distance between the cities if the cities are 12.7 cm apart on the map.
Let the actual distance be
.
So, we set a proportion to find the actual distance:
4.5:12.7 = 75:x.
<em>Changing into fractions.</em>
![\frac{4.5}{12.7} =\frac{75}{x}](https://tex.z-dn.net/?f=%5Cfrac%7B4.5%7D%7B12.7%7D%20%3D%5Cfrac%7B75%7D%7Bx%7D)
<em>By cross multiplication we get:</em>
![4.5x=952.5](https://tex.z-dn.net/?f=4.5x%3D952.5)
<em>Dividing both sides by 4.5 we get:</em>
![x=211.67](https://tex.z-dn.net/?f=x%3D211.67)
Therefore, the actual distance between the cities is 211.67 cm.
![\dfrac{x^3+10x^2+13x+39}{x^2+2x+1}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E3%2B10x%5E2%2B13x%2B39%7D%7Bx%5E2%2B2x%2B1%7D)
, and
. Subtracting this from the numerator gives a remainder of
![(x^3+10x^2+13x+39)-(x^3+2x^2+x)=8x^2+12x+39](https://tex.z-dn.net/?f=%28x%5E3%2B10x%5E2%2B13x%2B39%29-%28x%5E3%2B2x%5E2%2Bx%29%3D8x%5E2%2B12x%2B39)
, and
. Subtracting this from the previous remainder gives a new remainder of
![(8x^2+12x+39)-(8x^2+16x+8)=-4x+31](https://tex.z-dn.net/?f=%288x%5E2%2B12x%2B39%29-%288x%5E2%2B16x%2B8%29%3D-4x%2B31)
is not a multiple of
, so we're done. Then
![\dfrac{x^3+10x^2+13x+39}{x^2+2x+1}=x+8+\dfrac{-4x+31}{x^2+2x+1}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E3%2B10x%5E2%2B13x%2B39%7D%7Bx%5E2%2B2x%2B1%7D%3Dx%2B8%2B%5Cdfrac%7B-4x%2B31%7D%7Bx%5E2%2B2x%2B1%7D)